1987
DOI: 10.1246/bcsj.60.4259
|View full text |Cite
|
Sign up to set email alerts
|

A High-Resolution Solid-State 13C NMR Study of the Secondary Structure of Linear (1→3)-β-d-Glucans: A Conformational Elucidation of Noncrystalline and Crystalline Forms by Means of Conformation-Dependent 13C Chemical Shifts

Abstract: The high-resolution solid-state 13C NMR spectra of annealed curdlan, a (1→3)-β-d-glucan, were recorded in order to obtain reference data on the 13C chemical shifts of the triple helix form, which would be useful for the conformational elucidation of two distinct noncrystalline forms, curdlan- and laminaran-types. It was found that the C-3 peak of crystalline annealed glucan is substantially displaced from that of noncrystalline starting powder, reflecting the conformational change. The laminaran-type conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

1988
1988
2010
2010

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 27 publications
2
17
0
Order By: Relevance
“…The spectra of dried and rehydrated samples are similar to the previously reported spectra (Fig. 3b and c) (Fyfe et al, 1984;Saito et al, 1987Saito et al, , 1989. On the other hand, some signals of the never-dried samples clearly split into more peaks than that of the rehydrated samples, although the peak positions of the two spectra are the same (Fig.…”
Section: Solid-state Cp/mas 13 C Nmr Spectroscopysupporting
confidence: 87%
See 2 more Smart Citations
“…The spectra of dried and rehydrated samples are similar to the previously reported spectra (Fig. 3b and c) (Fyfe et al, 1984;Saito et al, 1987Saito et al, , 1989. On the other hand, some signals of the never-dried samples clearly split into more peaks than that of the rehydrated samples, although the peak positions of the two spectra are the same (Fig.…”
Section: Solid-state Cp/mas 13 C Nmr Spectroscopysupporting
confidence: 87%
“…One of the peaks might be derived from crystalline region and the other from amorphous region. However, Saito et al (1987) reported that the relaxation time (T 1c ) of those two peaks was almost the same: 26 and 34 s; therefore it is impossible to assign one of them to amorphous region. Further study is required on this point.…”
Section: Solid-state Cp/mas 13 C Nmr Spectroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…A member of the 1-3-␤-d-glucan family laminarin has a linear structure with a small degree of side branching. Laminarin is an uncharged polysaccharide at neutral pH, which has been shown to form a triple helical conformation under these conditions in water [5][6][7][8]. The structures reported in this study are formed by drying neutral pH solutions of laminarin onto clean mica.…”
Section: Introductionmentioning
confidence: 99%
“…It is pointed out that direct NMR observation of the solid-like domains has recently been made possible (14,15) by the development of a highly stable magic-angle spinning system using a rotor of the double air bearing type. In the present article, we summarize our previous results on conformation and dynamics of (1 -• 3)-/?-d-glucans in the solid and gel states (15)(16)(17)(18)(19)(20)(21)(22) by conventional and high-resolution solid-state 13 C NMR, with emphasis on revealing gelation mechanisms.…”
Section: Saitômentioning
confidence: 98%